The first documentation of Li-Fraumeni syndrome in Korea. - Bang, Y. J. (Korean Academy of Medical Sciences, 1995)
Li-Fraumeni syndrome(LFS) is an autosomal dominant disorder that predisposes individuals to multiple forms of cancer including breast cancer, soft tissue sarcoma, brain tumor, osteosarcoma, leukemia, and adrenocortical carcinoma. Recently, germ-line mutation of the p53 tumor suppressor gene has been implicated in this familial disorder. We report a case of a 25-year old woman who presented with bilateral breast cancer and uterine leiomyoma. Her mother had died of early-onset bilateral breast cancer. And her younger sister had breast carcinoma as well, which was identified at the age of 22, indicating her strong familial history. To test for the presence of the p53 germ-line mutation, we analyzed the genomic DNA from the peripheral blood of the proband and her sister by PCR-SSCP analysis of exon 5 through exon 8 of the p53 gene. As a result, a p53 mutation in exon 7 was detected in an allele, and it was shared with her sister as the same pattern. Sequencing analysis determined the altered nucleotide at codon 248(CGG > TGG) which is one of the most frequent mutation sites related to LFS. Therefore, this patient has the most consistent characteristic features of LFS phenotype and it is believed that this case is the first report of a family with Li-Fraumeni syndrome carrying the p53 germ-line mutation in Korea.